A descriptive case series of HIV-positive infants started on antiretroviral treatment within the first six weeks of life at Rahima Moosa Mother and Child Hospital - Goossens Carice Ann (My University, 2018)
Background: Human Immunodeficiency Virus (HIV) progresses rapidly in neonates (babies younger than 28 days of life), often before, the previously recommended, routine HIV testing at six weeks and subsequent treatment initiation. Recent South African treatment guidelines recommend HIV polymerase chain reaction (PCR) testing on all HIV-exposed babies at birth and recommend starting antiretroviral treatment (ART) within one week of diagnosis. This results in babies being diagnosed and treated much earlier than previously. There is inadequate evidence around the safe and effective use of ART in neonates, especially in premature infants. The presence of concurrent illnesses complicates the initiation of ART and affects treatment outcomes. The effectiveness and adverse effects of ART in infants where the pharmacokinetics and pharmacodynamics of ART are poorly understood need to be documented. The aim of this study was to describe the diagnosis, treatment, and outcomes of HIV-infected neonates initiated on ART within the first six weeks of life at Rahima Moosa Mother and Child Hospital (RMMCH), Johannesburg, South Africa. Subjects and Methods: Records of neonates initiated on ART prior to 6 weeks of age between 2004 -2013 were reviewed. These neonates were tested earlier than prevailing national guidelines due to their being symptomatic for HIV infection, being premature, or having low birth weight (LBW). Sixty-two files where neonates had a positive PCR test prior to 6 weeks of life were reviewed. Cases were excluded if either they were started on ART in the first six weeks of life at a different institution or if they were not cared for at RMMCH in their first year of life. A number of patients were excluded due to initiation after 6 weeks even though diagnosed prior. Baseline pretreatment characteristics (PMTCT exposure, clinical parameters, and clinical conditions at ART initiation) were reviewed. Outcomes to the end of one year of life with regards to follow-up status, clinical parameters (weight and height Z-scores), and immunological and virological results (CD4 and VL) were reviewed. Results: Twenty records were eligible and reviewed. The median age of ART initiation was 27 days. The majority of patients fulfilling the study criteria were premature, LBW infants who had received inadequate PMTCT. Fourteen neonates required treatment for illnesses prior to or during the period of ART initiation. Two of these newborns required ventilation. Illnesses requiring treatment were: necrotizing enterocolitis (n=2), neonatal hepatitis (n=1 ), congenital pneumonia (n=3), congenital syphilis (n=2), cytomegalovirus infection (CMV) (n=2), pneumocystis jirovecii pneumonia (PCP) (n=2), tuberculosis (n=2) and Group B Streptococcus meningitis (n=1) Other pre-treatment characteristics such as adequate PMTCT (n=3}, prematurity (n=12}, LBW(n=10), thrombocytopenia (n=6), anemia (n=8) and renal dysfunction (n=2) were evident. Viral load (VL) pre-ART ranged from 1295-10 000 000 copies/ml. One nevirapine-exposed infant had an undetectable VL immediately pre-ART even though HIV was confirmed virologically in prior and later tests. Abacavir (ABC), 3TC, and LPV/r was the most common regimen initiated. (n=10). Two patients were demised. Lipodystrophy was an adverse effect experienced by one patient on stavudine (d4T}. Conclusion: In our study of mainly premature and LBW neonates who initiated ART at a mean age of 28 days (SD: 11 days) we saw that many of them had significant co-morbidities. The majority of patients initiated early in this study survived until 1-year follow-up, two demised. This study highlights the need for consideration and further research of co-morbid conditions at the time of ART initiation as well as adverse effects of medication and polypharmacy. Reduced diagnostic sensitivity in nevirapine-exposed infants may be a concern in infants tested after birth.
A research report submitted to the Faculty of Health Sciences, University of Witwatersrand, Johannesburg, in partial fulfillment of the requirements for the degree of Master of Medicine in the branch of Paediatrics